Alterations In Biochemical Parameters Of Wister Rats Administered With Sulfadoxine And Pyrimethamine (FansidarR) - Nnodim Johnkennedy*, Emejulu Adamma, Amaechi Austin and NwosuNjoku Emmanuel Chukwunyere (Al Ameen Medical College, 2010)
Sulfadoxine and pyrimethamine(FansidarR) is commonly prescribed for the treatment of malaria in Owerri, Imo State Nigeria. This study examined the biochemical effect of Fansidar on the hepatic and renal function of wistar rats. Different concentrations of FansidarR (50, 100 and 150mg/kg body weigth) were administered to three groups of six wistar rats per group for 14 days. The fourth group of another six wistar rats received distilled water which served as control. Results showed that the FansidarR treated groups exhibited a significant increase in mean serum urea and creatinine levels when compared with the control group. This study also revealed that the administration of FansidarR caused pronounced increase in serum aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase as well as bilirubin levels. This study suggests that acute administration of Fansidar may probably affect both renal and hepatic function in humans.